The Implementation of Organization Development at PT Pembangkitan Jawa-Bali - Puri Handoko (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
Background – PT Pembangkitan Jawa-Bali (PT PJB) is a subsidiary of PT PLN (Persero) which participates in the Business Performance Rating Program in Environmental Management (PROPER) organized by the Ministry of Environment and Forestry (MoEF) of the Republic of Indonesia based on Ministry of Environment Regulation No 06 year 2013. As a subsidiary of PT PLN (Persero), PT PJB establishes management contracts which aim to get a Gold PROPER rating from the MoEF. Even so, the company still has some challenges as it encounters several problems of managing CSR internally. As a first step, PT PJB, especially in CSR Department, has made improvements in its organization by implementing a PROPER-based performance appraisal system in managing CSR in all PT PJB Power Plants. Purpose – Examining the phenomenon which has been occurring for the past several years, researcher decided to conduct observations and interviews. This study tries to explain descriptively how changes have been designed and implemented through the